2012
DOI: 10.1371/journal.pone.0053032
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Dosage of Oral Alendronate Will Increase the Subsequent Cancer Risk of Osteoporosis Patients in Taiwan: A Population-Based Cohort Study

Abstract: BackgroundControversy still exists regarding whether alendronate (ALN) use increases the risk of esophageal cancer or breast cancer.MethodsThis paper explores the possible association between the use of oral ALN in osteoporosis patients and subsequent cancer risk using the National Health Insurance (NHI) system database of Taiwan with a Cox proportional-hazard regression analysis. The exposure cohort contained 5,624 osteoporosis patients used ALN and randomly frequency-matched by age and gender of 3 osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 21 publications
2
35
1
Order By: Relevance
“…To assess any association between the duration of bisphosphonate use and the risk of endometrial cancer, we used the available data from three cohort studies and two case–control studies . Results showed no risk reduction in the shortest bisphosphonate exposure (less than 1 year) (RR 0.92, 95%CI 0.64–1.34).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess any association between the duration of bisphosphonate use and the risk of endometrial cancer, we used the available data from three cohort studies and two case–control studies . Results showed no risk reduction in the shortest bisphosphonate exposure (less than 1 year) (RR 0.92, 95%CI 0.64–1.34).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [13][14][15][16][17][18]30 met the inclusion criteria and were included in this meta-analysis ( Figure 1), including four cohort studies [14][15][16]18 and three case-control studies. 13,17,30 .…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of reduced gastric cancer incidence among bisphosphonate users was replicated by several other studies, including one which found a 39% reduction in the risk of gastric cancer, although a recent meta‐analysis reported no overall effect . Several studies investigating the effect of bisphosphonate use on cancer incidence, separately for both the oesophageal and gastric sites, reported a similar pattern to our study ( i.e ., increased risk of oesophageal cancer which was largely offset by a decreased risk of gastric cancer) …”
Section: Discussionmentioning
confidence: 97%